Subcellular localization of T-cell receptor complexes containing tyrosine-phosphorylated zeta proteins in immature CD4+CD8+ thymocytes. - Kearse, K P (1993)
The T-cell antigen receptor (TCR) is a complex of at least six different proteins (alpha, beta, gamma, delta, epsilon, and zeta) that is assembled in the endoplasmic reticulum (ER) and transported to the cell surface. Unlike mature T cells, most immature CD4+CD8+ thymocytes retain within the ER and degrade greater than 90% of some of the TCR components they synthesize, resulting in low surface expression of TCR complexes. The few surface TCR complexes that most immature CD4+CD8+ thymocytes do express are only marginally capable of transducing signals mobilizing intracellular calcium. The inverse relationship with TCR expression and function suggested that phosphorylated zeta (P-zeta) molecules might function in CD4+CD8+ thymocytes either as an ER retention signal for newly synthesized TCR complexes or as a negative regulatory modification of TCR complexes present on the cell surface. The present study sought to evaluate these two possibilities by determining the subcellular location of TCR complexes containing P-zeta chains. We found that, unlike unmodified zeta chains, all P-zeta chains in CD4+CD8+ thymocytes existed in assembled TCR complexes and that all TCR complexes containing P-zeta molecules had undergone carbohydrate processing events indicative of transit through the Golgi apparatus. These results demonstrate that P-zeta chains are exclusively associated with mature TCR complexes, excluding the possibility that P-zeta serves as an ER retention signal in immature thymocytes. Although we could not directly determine the representation of P-zeta chains among surface TCR complexes, we found that 60-70% of surface TCR complexes on immature CD4+CD8+ thymocytes were associated with tyrosine-phosphorylated protein(s) and that this percentage was inversely correlated with their signaling competence. These results support the concept that tyrosine phosphorylation serves as a negative regulatory modification of certain TCR-associated proteins.